Abdominal Wall Endometrioma. Report of Two Cases - Tahiluma Santana Pedraza; Jorge Luís Estepa Pérez; Juan Carlos Estepa Torres (Medisur)
Abdominal wall endometrioma is a condition rarely seen by surgeons. It represents a diagnostic challenge due to its similarity with other tumors. This entity occurs in fertile women and often appears two to five years after gynecological and obstetric surgical procedures. It must be considered when dealing with a cyclically painful nodule located in a laparotomy scar. The diagnosis is established by histological examination; most imaging tests determine the characteristics of the lesion, concomitant lesions and the intra-abdominal origin or location in the abdominal wall. The cases of two patients treated at the General Surgery Department of the María Eugenia González Comprehensive Diagnostic Center in the Capital District, Venezuela, are presented. Wide excision of the tissue and histological examination were performed, confirming the diagnosis. The postoperative course was uneventful. This case is presented given the rarity of this condition.